The Role of Exposure to Neighborhood and School Poverty in Understanding Educational Attainment. - Nieuwenhuis, Jaap; Kleinepier, Tom; van Ham, Maarten (Journal of Youth & Adolescence, 2021)
Because the demographic composition of neighborhoods and schools overlaps, their effects on educational attainment are not independent of each other. Throughout the early teenage years, the timing and duration of exposure to neighborhood and school contexts can vary, advocating for a longitudinal approach when studying schooling outcomes. This study uses Avon Longitudinal Study of Parents and Children data (N = 4502; 49% female) to examine how exposure to poverty between ages 10–16 predicts educational attainment. The results indicate that enduring exposure to neighborhood poverty relates to educational attainment, while timing does not. For school poverty, longer exposure is related to lower attainment, but earlier exposure has a stronger impact than later exposure. Adolescents who were exposed to poverty in both contexts for the full observation period had the lowest educational attainment. The findings highlight the importance of understanding when and how long adolescents are exposed to contextual poverty.